The Moral View of Islamic Education in the Book "Religious Logic: The Position of Revelation and the Limits of Reason in Islam" by M. Quraish Shihab - Toriq Zainul Asri; Muh. Zakaria (EDUJAVARE: International Journal of Educational Research, 2026)
The moral decline among students in the modern era shows the importance of strengthening moral education based on Islamic values. One of the fundamental problems in Islamic moral education is the relationship between revelation and reason as a source of determining moral values. This research aims to find out and describe how the moral view of Islamic education in the book of religious logic. This research uses a philosophy of religion approach with the type of library research. The primary data source is in the form of the book Religious Logic by M. Quraish Shihab, while secondary data is obtained from various relevant books, journals, and literature. The data collection technique was carried out through documentation studies and literature review. Data analysis uses the content analysis method. The results of the study show that the morality of Islamic education is built on a harmonious relationship between revelation and reason. Revelation is positioned as the main source of moral values, while reason functions to understand, develop, and actualize these values in life. The findings of the study reveal five main aspects, namely revelation-based morality, the role of reason in moral formation, the integration of revelation and reason, education as a means of character formation, and the relevance of Islamic morality to modern challenges. M. Quraish Shihab's thinking offers an integrative, moderate, and contextual moral education paradigm, so that it is able to answer the needs of Islamic education in forming students who are moral, critical, and responsible.